2014
DOI: 10.2503/jjshs1.mi-008
|View full text |Cite
|
Sign up to set email alerts
|

SEM Observation of Wet Lily Pollen Grains Pretreated with Ionic Liquid

Abstract: Mature pollen grains of Lilium cultivar, with their germ pores folded in upon themselves, were observed under a scanning electron microscope (SEM). The conventional pretreatment process requires aldehyde fixation, dehydration, drying and metal sputtering for SEM observation. These complicated and laborious procedures can considerably alter the morphology of pollen grains. In order to omit this conventional pretreatment process, we established a novel technique utilizing an ionic liquid (IL) that is composed so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In addition, electrostatic interactions seem to be involved in the adhesion of pollen grains to the surface of insect pollinators. 35 Using scanning electron microscopy (SEM), Komai et al 36 recently demonstrated that an ionic liquid can be coated uniformly on wet Lilium pollen grains, probably as a result of multiple ionic interactions. 37 Thus, we believe that the synthesized ILGs have an ideal structure for effective pollen adsorption.…”
Section: Synthesis and Characterization Of Ilgsmentioning
confidence: 99%
“…In addition, electrostatic interactions seem to be involved in the adhesion of pollen grains to the surface of insect pollinators. 35 Using scanning electron microscopy (SEM), Komai et al 36 recently demonstrated that an ionic liquid can be coated uniformly on wet Lilium pollen grains, probably as a result of multiple ionic interactions. 37 Thus, we believe that the synthesized ILGs have an ideal structure for effective pollen adsorption.…”
Section: Synthesis and Characterization Of Ilgsmentioning
confidence: 99%
“…al. noted that highly concentrated RTILs can effectively hide surface features from observation and found that low concentrations of 1 % and 5 % [Ch][Lac]‐ethanolic solutions provided improved resolution in imaging hydrated, unfixed mature pollen grains of Lilium cultivar in SEM [48] …”
Section: Introductionmentioning
confidence: 99%
“…In addition, ILs can also have very high electrical conductivity [3]. As such they are used in many applications which take advantage of one or both of these attributes, including wetting agents in high-vacuum electron microscopy studies [4][5][6][7], battery electrolytes [8][9][10], and as propellants for electrospray spacecraft propulsion [11][12][13][14][15][16][17][18][19]. In spacecraft that utilize IL electrospray, extreme electric fields are applied to the free surface of an IL in order to extract and accelerate ions and/or droplets.…”
Section: Introductionmentioning
confidence: 99%